NaCl Pretreatment Enhances the Low Temperature Tolerance of Tomato Through Photosynthetic Acclimation - Yang, Xiaolong; Zou, Fengyu; Zhang, Yumeng; Shi, Jiali; Qi, Mingfang; Liu, Yufeng; Li, Tianlai (Frontiers in Plant Science, 2022)
Plants often need to withstand multiple types of environmental stresses (e.g., salt and low temperature stress) because of their sessile nature. Although the physiological responses of plants to single stressor have been well characterized, few studies have evaluated the extent to which pretreatment with non-lethal stressors can maintain the photosynthetic performance of plants in adverse environments (i.e., acclimation-induced cross-tolerance). Here, we studied the effects of sodium chloride (NaCl) pretreatment on the photosynthetic performance of tomato plants exposed to low temperature stress by measuring photosynthetic and chlorophyll fluorescence parameters, stomatal aperture, chloroplast quality, and the expression of stress signaling pathway-related genes. NaCl pretreatment significantly reduced the carbon dioxide assimilation rate, transpiration rate, and stomatal aperture of tomato leaves, but these physiological acclimations could mitigate the adverse effects of subsequent low temperatures compared with non-pretreated tomato plants. The content of photosynthetic pigments decreased and the ultra-microstructure of chloroplasts was damaged under low temperature stress, and the magnitude of these adverse effects was alleviated by NaCl pretreatment. The quantum yield of photosystem I (PSI) and photosystem II (PSII), the quantum yield of regulatory energy dissipation, and non-photochemical energy dissipation owing to donor-side limitation decreased following NaCl treatment; however, the opposite patterns were observed when NaCl-pretreated plants were exposed to low temperature stress. Similar results were obtained for the electron transfer rate of PSI, the electron transfer rate of PSII, and the estimated cyclic electron flow value (CEF). The production of reactive oxygen species induced by low temperature stress was also significantly alleviated by NaCl pretreatment. The expression of ion channel and tubulin-related genes affecting stomatal aperture, chlorophyll synthesis genes, antioxidant enzyme-related genes, and abscisic acid (ABA) and low temperature signaling-related genes was up-regulated in NaCl-pretreated plants under low temperature stress. Our findings indicated that CEF-mediated photoprotection, stomatal movement, the maintenance of chloroplast quality, and ABA and low temperature signaling pathways all play key roles in maintaining the photosynthetic capacity of NaCl-treated tomato plants under low temperature stress.